2014
DOI: 10.1111/hdi.12128
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between docosahexaenoic acid and mortality in patients on hemodialysis during over 10 years

Abstract: We have previously conducted a cohort study to investigate n-3 polyunsaturated fatty acids (PUFAs) in red blood cells (RBCs) and risk of all-cause mortality in hemodialysis (HD) patients over 5 years and found that n-3 PUFAs, especially docosahexaenoic acid (DHA), might be an independent predictor of all-cause mortality. In the present study, we extended the study for another 5 years to determine whether DHA levels in RBCs still predict the mortality of HD patients during a 10-year study period. The study coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
(64 reference statements)
1
13
0
Order By: Relevance
“…Briefly, a total of 493 independent citations were identified after duplicate exclusion, of which 32 were retrieved for full-text review. Ten publications were excluded because the exposure or outcome was not relevant to the topic we studied; 11 reports were excluded because they investigated dietary/circulating n-3 LCPUFA among patients with certain diseases, such as type 2 diabetes 23 24 , CHD 25 26 27 28 , heart failure 29 30 , and kidney disease 31 32 33 ; further excluded was one publication 34 which was an overlapping report of another 35 with larger events. Finally, 10 publications 13 14 15 16 17 18 19 20 21 22 including 11 independent prospective studies (2 cohorts were combined in one publication 17 ) were included in this meta-analysis, involving 7 studies 13 14 15 16 17 18 on dietary n-3 LCPUFA and 4 studies 19 20 21 22 on circulating EPA/DHA in relation to all-cause mortality risk.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, a total of 493 independent citations were identified after duplicate exclusion, of which 32 were retrieved for full-text review. Ten publications were excluded because the exposure or outcome was not relevant to the topic we studied; 11 reports were excluded because they investigated dietary/circulating n-3 LCPUFA among patients with certain diseases, such as type 2 diabetes 23 24 , CHD 25 26 27 28 , heart failure 29 30 , and kidney disease 31 32 33 ; further excluded was one publication 34 which was an overlapping report of another 35 with larger events. Finally, 10 publications 13 14 15 16 17 18 19 20 21 22 including 11 independent prospective studies (2 cohorts were combined in one publication 17 ) were included in this meta-analysis, involving 7 studies 13 14 15 16 17 18 on dietary n-3 LCPUFA and 4 studies 19 20 21 22 on circulating EPA/DHA in relation to all-cause mortality risk.…”
Section: Resultsmentioning
confidence: 99%
“…However, an observational study [44] has suggested DHA in red blood cells to be an independent predictor of mortality in end stage renal disease patients on hemodialysis after 10 years of follow-up. Also, a clinical controlled trial found 2 years of n -3 PUFA treatment to be beneficial in secondary prevention of myocardial infarction in chronic HD patients, while no effect was seen on the primary endpoint, a composite of total cardiovascular events and death [45].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study found a trend between a erythrocyte omega 3 index levels and survival amongst HD patients; however, the fact that this did not reach statistical significance may be ascribed to an insufficient cohort size to achieve adequate statistical power [180]. Recent longitudinal observational cohort studies have found that the DHA content of erythrocyte plasma membranes is able to independently predict mortality outcomes in HD patients [181,182]. Other studies investigating the fatty acid profile of the serum and mortality in HD patients may be predicted by serum DHA levels [183] or the ratio between n -3 and n -6 [184].…”
Section: Omega-3 Polyunsaturated Fatty Acids (N-3 Pufas)mentioning
confidence: 99%